Perioperative fatal pulmonary embolism in a pediatric liver transplant recipient. (27th March 2021) - Jamil, Omar; Fung, John; Kelly, Dympna; Azzam, Ruba
Abstract: Patients with cirrhotic liver disease are in a state of fluctuating hemostatic balance. Hepatic synthetic dysfunction is commonly complicated by coagulation disorders that constitute an important parameter of most prognostic scores. The dominant feature of this dysfunction is bleeding tendencies, but cirrhotic patients may also exhibit inappropriate clotting and pro‐coagulation placing them at risk for thromboembolism. We present a case of perioperative fatal pulmonary embolism in an 8‐year‐old patient with biliary cirrhosis secondary to drug‐induced vanishing bile duct syndrome undergoing a deceased donor liver transplant. The massive pulmonary embolism occurred intra‐operatively after reperfusion of the donor liver. Despite the initiation of extracorporeal membrane oxygenation, the postoperative course was complicated by bleeding and the patient expired. This unique case highlights the need for venous thromboembolism prevention by screening and prophylaxis prior to liver transplant in at least a subpopulation of pediatric patients. While the risk of thrombosis postoperatively in pediatrics patients is well known, the preoperative risk is less frequently described and deserves attention and practice changing action.